1988
DOI: 10.1902/jop.1988.59.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Immunological Studies of Adult Periodontitis in Patients with Noninsulin‐Dependent Diabetes Mellitus

Abstract: The subgingival microflora and serum antibody response was examined in Periodontitis patients with noninsulin‐dependent diabetes mellitus (NIDDM), impaired glucose tolerance (IGT), and normal glucose tolerance (NGT). The predominant cultivable microflora was determined for subgingival plaque sampled from two deep periodontal pockets in each of eight adult Periodontitis patients with NIDDM. Indirect immunofluorescence for Bactewides intermedius, Bacteroides gingivalis, and Haemophilus actinomycetemcomitans was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 45 publications
(5 reference statements)
7
119
1
3
Order By: Relevance
“…51,52 It is a frequent isolate from endodontic infections 53,54 and pregnancy gingivitis, 55 and has been associated with the periodontal breakdown in Type I diabetics. 56 This organism has also been observed in nonoral infections such as pleuropulmonary infections and abscesses of the head and neck. 57,58 Intraspecies heterogeneity has been demonstrated for P. intermedia, where two distinct DNA homology groups have been observed.…”
Section: Discussionmentioning
confidence: 98%
“…51,52 It is a frequent isolate from endodontic infections 53,54 and pregnancy gingivitis, 55 and has been associated with the periodontal breakdown in Type I diabetics. 56 This organism has also been observed in nonoral infections such as pleuropulmonary infections and abscesses of the head and neck. 57,58 Intraspecies heterogeneity has been demonstrated for P. intermedia, where two distinct DNA homology groups have been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were reported by a study in Pima Indians which showed type 2 diabetes was associated with severity of periodontitis independent of age. 17 Gender is considered as one of the confounding factors in periodontitis. 2 A study reported higher prevalence of periodontitis in males due to tobacco use and higher incidence in females due to effect of progesterone and oestrogen interplay on periodontium.…”
Section: Methodsmentioning
confidence: 99%
“…
Bacteroides (Porphyromonas) gingivalis and Bacteroides (Porphyromonas) intermedius are metabolically diverse species of gram-negative anaerobic bacilli implicated in the etiology of human periodontal diseases (14,25,33,35). These diseases are characterized by gingival inflammation and loss of connective tissue and bone from around the roots of the teeth (13).
…”
mentioning
confidence: 99%